Functional material based on red mud waste loaded Fe-MOF, preparation method and application

By using red mud as a carrier and loading Fe-MOF, the composite functional material RM-MIL is solved, and the effective utilization of red mud and efficient treatment of organic pollutants in sewage is achieved.

CN119500269APending Publication Date: 2025-02-25ZHONGYUAN ENGINEERING COLLEGE
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411529288.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively utilize industrial waste red mud, which leads to the emission and storage of red mud, and the comprehensive utilization rate of red mud is relatively low.

Method used

By using red mud as a support and using in-situ composite method to load Fe-MOF, a composite functional material RM-MIL was prepared and developed a process for photocatalyzing treatment of organic pollutants in wastewater.

Benefits of technology

It realizes the effective utilization of red mud, reduces the pollution of red mud to the environment, and shows excellent results in photocatalytic treatment of organic pollutants, expanding the application fields of industrial waste and MOF materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500269A_ABST
    Figure CN119500269A_ABST
Patent Text Reader

Abstract

The invention discloses a functional material based on red mud waste loaded Fe-MOF as well as a preparation method and application of the functional material. At present, when a bayer process is adopted to smelt bauxite to obtain a metal material aluminum in industry, a solid waste named red mud can be generated. The accumulation of a large amount of red mud can cause serious pollution to the environment. Therefore, the invention provides a method for preparing a catalytic material based on acidified aluminum industrial waste red mud composite Fe-MOF and a treatment process of pollutants in a water environment. The composite material RM-MIL is prepared through an in-situ compounding method, and the composite material can remove 97.6% of organic pollutants in environmental water in an adsorption-degradation process. The composite material and the treatment process thereof developed by the invention have wide application value in the field of sewage treatment, and a feasible method is provided for resource development of the waste red mud by the Bayer process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalytic treatment of pollutants and utilization of industrial waste, and specifically to a functional material based on red mud waste loaded Fe-MOF, a preparation method and application thereof, and is a study of the application of composite materials constructed by Bayer process waste red mud and Fe-based organic frameworks in the photocatalytic treatment of pollutants. Background Art

[0002] Red mud is a solid industrial waste generated during the alumina extraction process from bauxite. It is called red mud because it is rich in iron oxide (20% to 50%) and has a reddish-brown color. As alumina production capacity has rapidly increased, red mud emissions have also been increasing. According to statistics, my country's cumulative red mud stockpiles have exceeded 350 million tons. Currently, most red mud is discharged through the "wet conveying-dry stacking" method, using dams and storage within storage yards. This not only occupies a large amount of land and incurs high construction and maintenance costs, but also poses safety risks to the surrounding soil and water environments. With society's increasing emphasis on environmental protection, the discharge and storage of red mud has become a major bottleneck restricting the development of the alumina industry.

[0003] With the development of the alumina industry, scholars at home and abroad have begun to conduct extensive research on the comprehensive utilization of red mud, and have achieved good results. Among them, the use of sintered red mud to produce Portland cement, bricks, and as a road base admixture; the recovery of iron from Bayer red mud, etc., have provided effective ways to reduce and utilize red mud from different perspectives and industry fields. However, the current global red mud utilization rate is approximately 15%, while the comprehensive utilization rate of red mud in my country is less than 4%. The large-scale and reduced-volume utilization of red mud remains a global challenge. Therefore, how to resolve the contradiction between technology and economic efficiency and find an economical and environmentally friendly reduction method is the key to the comprehensive utilization of red mud.

[0004] Red mud has the advantages of large specific surface area, fine particle size, and strong adsorption capacity, and is a potential low-cost adsorbent. Studies have found that red mud can remove toxic heavy metals, inorganic anions, phenolic compounds, bacteria, organic dyes, etc. from water, and has good application prospects in water treatment. For example, Pepper et al. used red mud to prepare red deer stone adsorbent to treat arsenic-contaminated water, and its performance was significantly better than similar adsorbents on the market. Deihimi et al. used activated red mud as a ferrocyanide adsorbent to remove ferrocyanide anions from aqueous solutions, and discussed the relationship between adsorption efficiency and ferrocyanide concentration, pH, adsorbent dosage, and contact time.

[0005] Furthermore, Bayer red mud is rich in metal oxides such as Fe2O3, Al2O3, and TiO2, which are typical active components of catalysts. Therefore, developing new catalysts from red mud is an effective approach for its regeneration and utilization. For example, Das et al. used calcined red mud as a catalyst in the transesterification reaction of dimethyl carbonate and glycerol, achieving ideal catalytic results. Red mud, with its small particle size and large specific surface area, is an ideal support for composite materials. For example, Jahromi et al. developed a red mud-supported nickel catalyst that efficiently catalyzes the hydrodeoxygenation of aqueous cypress catalytic cracking oil. These exemplary cases of "using waste to treat waste" provide valuable insights into the development and utilization of red mud.

[0006] To achieve resource utilization of industrial waste red mud and reduce its environmental pollution, this paper uses red mud as a carrier, loads an iron-based metal-organic framework (MOF) material via an in-situ composite method, and prepares a composite functional material (RM-MIL) to treat organic pollutants in wastewater. The composite material and its treatment process developed in this paper have broad application value in the field of wastewater treatment and provide a feasible method for the resource development of Bayer process waste red mud. Summary of the Invention

[0007] To address the challenges of the existing technology, the present invention provides a method for preparing a functional material based on a composite of red mud waste and Fe-MOF, and a process for treating pollutants in an aquatic environment. Specifically, the present invention provides a structurally stable composite material based on red mud waste and Fe-MOF, which can be used for efficient photocatalytic treatment of wastewater pollutants.

[0008] The present invention uses FeCl3·6H2O as an Fe source and 2-aminoterephthalic acid as an organic ligand to compound with acidified Bayer red mud to produce a composite material RM-MIL. This material is then used as a photocatalyst to treat organic pollutants in wastewater, effectively utilizing the waste red mud.

[0009] In order to solve the above technical problems, the present invention adopts the following solutions:

[0010] A composite material based on industrial waste red mud and Fe-MOF, wherein the photocatalytic material is in solid powder form. The microstructure is a rod-shaped crystalline Fe-MOF (MIL) supported on a block of red mud. The Fe-MOF is synthesized in a solution containing acidified Bayer red mud, with FeCl3·6H2O providing Fe 3+ The ionic center is embedded in the red mud and the ligand, and the three are interconnected to build a three-dimensional framework Fe-MOF structure loaded with red mud.

[0011] Furthermore, when not loaded with red mud, the particle size of Fe-MOF (MIL) alone is 2 μm, and after being loaded with red mud, the particle size increases to 4.5 μm.

[0012] The present invention also provides a method for preparing the photocatalytic material based on red mud waste loaded Fe-MOF, comprising the following steps:

[0013] (1) Acid treatment of red mud: A certain amount of dry red mud was fully ground and dispersed in a container containing distilled water. The solution was stirred using an orbital oscillator and the pH of the solution was adjusted to 5. The resulting turbidity was heated to boiling to obtain semi-dried red mud, which was then dried to obtain acidified red mud powder.

[0014] (2) Preparation of photocatalytic materials based on red mud waste loaded Fe-MOF: Acidified red mud powder was added to disperse Fe 3+ The Fe-MOF (MIL)-loaded functional material, namely the composite photocatalytic material RM-MIL, was obtained by high-temperature reflux reaction in a DMF solution with 2-aminoterephthalic acid as the metal center and ligand. After the reaction was completed, the material was cooled to room temperature, centrifuged, washed and dried to obtain the Fe-MOF (MIL)-loaded functional material, namely the composite photocatalytic material RM-MIL.

[0015] Furthermore, in the step (2), FeCl3·6H2O is used as Fe 3+ The source was first prepared by Fe-MOF to obtain its yield, and based on this, the amount of FeCl3·6H2O, 2-aminoterephthalic acid and acidified red mud powder added when preparing the functional material was determined. The results showed that the ideal conditions for preparing red mud waste loaded Fe-MOF (MIL) functional material were: the molar ratio of FeCl3·6H2O to 2-aminoterephthalic acid was 1:1, and the amount of acidified red mud powder added was twice the sum of the masses of FeCl3·6H2O and 2-aminoterephthalic acid.

[0016] Furthermore, in the step (2), the temperature of the high-temperature reflux reaction is 120° C., and the reflux reaction time is 4 hours.

[0017] The typical preparation method of the functional material based on red mud waste loaded Fe-MOF of the present invention comprises the following steps:

[0018] (1) Acid treatment of red mud: The red mud was dried in an oven, 10 g of dried red mud was weighed, ground for 5 min, and dispersed in a container containing 30 mL of distilled water. Concentrated hydrochloric acid was slowly added dropwise, and the mixture was stirred on an orbital oscillator. The pH value of the supernatant was continuously measured until the pH was ≈ 5. The solution was then evaporated to dryness to obtain acidified red mud powder.

[0019] (2) Synthesis of the composite material (RM-MIL): Acidified red mud powder (0.6 g) and 2-aminoterephthalic acid (0.7 mmol) were weighed and dissolved in 15 mL of N,N-dimethylformamide. After stirring for 1 h, FeCl3·6H2O (0.7 mmol) was weighed and added to the solution. The mixture was refluxed at 120°C for 4 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged. The mixture was washed with DMF and anhydrous ethanol, respectively. After centrifugation, the mixture was dried in a vacuum oven at 60°C for 12 h to obtain the RM-MIL product.

[0020] The present invention also provides the application of the Bayer red mud-and-Fe-MOF composite catalyst for the photocatalytic treatment of organic pollutants in aqueous environments. Under light-shielded conditions, the adsorption performance of the RM-MIL composite material for model dyes such as methylene blue, methyl violet, rhodamine B, and gentian violet was studied. The effect of red mud addition on the Fe-MOF was analyzed using Langmuir and Freundlich isothermal adsorption models, as well as pseudo-first-order and pseudo-second-order kinetic models. In the test, 5 mg of the red mud waste-loaded Fe-MOF functional material was added to 20 mL of various dyes at a concentration of 20 mg / L. The dyes were then poured into a conical flask and adsorption was carried out on an oscillator. Every hour, 5 mL of the solution was centrifuged from the conical flask, and the supernatant was tested to measure the absorbance of the various dyes.

[0021] This study investigates the adsorption of organic pollutants in wastewater by a composite material, RM-MIL, prepared by combining waste red mud with Fe-MOF. The photocatalytic degradation of methylene blue (MB) was investigated using methylene blue as a model pollutant. 5 mg of sample was added to a 20 mL methylene blue solution, and after reaching adsorption equilibrium, the sample was tested in a multifunctional photochemical reactor. During the photocatalytic degradation of the methylene blue dye, a 500W mercury lamp was used as the light source. Every 30 minutes, 5 mL of the solution was aspirated from the reaction system and centrifuged. The supernatant was then collected and its absorbance measured. Throughout the experimental analysis, the composite material demonstrated an adsorption capacity of 73.28 mg / g for methylene blue, with a total removal rate of 97.6%.

[0022] Red mud has a small particle size and a large specific surface area, making it suitable for use as a composite material carrier. Furthermore, red mud itself contains a variety of metal oxides, such as Fe2O3, Al2O3, and TiO2, which are typical active components of catalysts. When combined with Fe-based metal-organic frameworks, these functional materials, such as Fe-MOFs (MILs), can be used to treat organic pollutants in environmental water through adsorption-photocatalysis, effectively utilizing waste resources.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The composite material RM-MIL of the present invention can effectively utilize the industrial pollutant red mud, save resources and reduce the pollution of red mud to the environment. At the same time, the excellent performance of this material in the photocatalytic treatment of organic pollutants expands the application field of industrial waste and MOF materials.

[0025] 2. The composite material RM-MIL provided by the present invention is prepared by a simple heating reflux process. The preparation method is simple and easy, and the photocatalytic treatment performance of sewage pollutants is stable, conforms to the Langmuir isotherm adsorption, belongs to the monolayer adsorption under the ideal adsorption system, and conforms to pseudo-second-order kinetics, indicating that it is mainly chemical adsorption, which can more effectively treat pollution sources.

[0026] 3. The composite material RM-MIL provided by the present invention can be mass-produced to reduce costs, providing a new option for treating organic pollutants in sewage. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0028] Figure 1 is the X-ray powder diffraction pattern of the composite material RM-MIL of Example 1.

[0029] Figure 2 is the infrared spectrum of the composite material RM-MIL of Example 1.

[0030] Figure 3 is a scanning electron microscope image of the composite material RM-MIL of Example 1.

[0031] Figure 4 This is the solid ultraviolet diffuse reflectance spectrum of the composite material RM-MIL of Example 1.

[0032] Figure 5 This is a graph showing the adsorption capacity of the composite material RM-MIL of Example 1 for different dyes.

[0033] Figure 6 Graphs showing the adsorption capacity and adsorption rate of the composite material RM-MIL of Example 1 compared with MIL at different initial concentrations (a) and the adsorption capacity (b) and adsorption rate (c) of methylene blue at different times.

[0034] Figure 7 Graphs showing the photodegradation curve (a) and photodegradation rate (b) of the composite material RM-MIL of Example 1 for methylene blue. Figure 8 (a) The Langmuir isotherm adsorption model fitting diagram of the composite material RM-MIL in Example 1 and (b) the Freundlich isotherm adsorption model fitting diagram.

[0035] Figure 9 These are the pseudo-first-order kinetic (a) and pseudo-second-order kinetic fitting diagrams (b) of the composite material RM-MIL in Example 1. DETAILED DESCRIPTION

[0036] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies implemented based on the contents of the present invention fall within the scope of the present invention.

[0037] Example 1

[0038] The preparation of a composite catalyst based on Bayer red mud and Fe-MOF in this embodiment is as follows:

[0039] (1) Red mud was dried in an oven. 10 g of dried red mud was weighed and ground for 5 min. The mixture was dispersed in a container containing 30 mL of distilled water. Concentrated hydrochloric acid was slowly added dropwise. The mixture was stirred on an orbital oscillator. The pH value of the supernatant was continuously measured until the pH was ≈ 5. The container was then placed on a heater and boiled until the red mud was half dry. The mixture was then dried in an oven.

[0040] (2) Acidified red mud powder (0.6 g) and 0.12 g of 2-aminoterephthalic acid (0.7 mmol) were weighed and dissolved in 15 mL of N,N-dimethylformamide. After stirring for 1 h, 0.18 g of FeCl3·6H2O (0.7 mmol) was weighed and added to the solution. The mixture was refluxed at 120°C for 4 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged. The mixture was washed with DMF and anhydrous ethanol, respectively. After centrifugation, the mixture was dried in a vacuum oven at 60°C for 12 h to obtain the RM-MIL product.

[0041] Synthesis of Fe-MOF (MIL): FeCl₃·6H₂O (0.7 mmol) and 2-aminoterephthalic acid (0.7 mmol) were dissolved in 15 mL of N,N-dimethylformamide and refluxed at 120°C for 4 h. After the reaction, the mixture was cooled to room temperature and centrifuged. The mixture was washed with DMF and anhydrous ethanol, respectively, and dried in a vacuum oven at 60°C for 12 h to obtain the MIL product.

[0042] 1. X-ray powder diffraction analysis of the composite material RM-MIL

[0043] The fully automatic combined powder polycrystalline X-ray diffractometer can determine the crystallinity and structure of the product, and the obtained XRD pattern is as follows Figure 1 As shown in the figure, red mud contains minerals such as calcite, aragonite, dicalcium silicate, tricalcium aluminate, and pyrite. The 2θ values ​​of the diffraction peaks of MIL are 9.2°, 12.5°, and 17.3°, and the composite material also exhibits diffraction peaks at the same positions. The composite material also has diffraction peaks at 33° and 36°, indicating that the composite material also contains minerals such as tricalcium aluminate and aragonite. This indicates that red mud and MIL have been successfully composited.

[0044] 2. Infrared spectroscopy analysis of composite material RM-MIL

[0045] Intelligent Fourier transform infrared spectrometer can measure the vibration absorption peaks of functional groups and chemical bonds in the structure of synthetic samples. The FT-IR spectrum of synthetic materials is as follows: Figure 2 As shown, the infrared spectra of the two materials are in the range of 4000-400 cm -1 There are similar absorption peaks in the range. At 3463cm -1 The absorption peak of NH bond is at 1496cm -1 The stretching vibration peak of the CN bond is at 1580cm -1 The absorption peak of the CC bond on the benzene ring skeleton is at 560cm -1 The absorption peak at 2-aminoterephthalic acid belongs to Fe-O vibration, which indicates that the carboxyl group of 2-aminoterephthalic acid is bound to Fe 3+ A coordination bond was formed between them, which confirmed the synthesis of the composite material RM-MIL.

[0046] 3. Scanning electron microscopy analysis of composite material RM-MIL

[0047] The morphology of the material can be observed by scanning electron microscopy. The SEM map of the material is as follows: Figure 3 As shown in the left image, MIL is a rod-shaped crystal with a particle size of 2 μm. The right image shows that rod-shaped crystals similar to MIL have grown in red mud with a particle size of 4.5 μm. The addition of red mud also increases the crystal size, indicating that red mud and MIL have successfully composited.

[0048] 4. UV analysis of composite material RM-MIL

[0049] Ultraviolet-visible diffuse reflectance spectroscopy can be used to determine the optical responsiveness and band gap width of the synthetic material. The DRS spectrum of the synthetic material confirms that the absorption peak of RM-MIL is basically between 200 and 400 nm, indicating that both materials respond in the ultraviolet and visible light regions.

[0050] The application of the composite catalyst based on Bayer red mud and Fe-MOF described in the present invention in the photocatalytic treatment of organic pollutants in wastewater: Under light-proof conditions, the adsorption performance of the RM-MIL composite material on model dyes such as methylene blue, methyl violet, rhodamine B, and gentian violet was studied, and the adsorption behavior was analyzed using Langmuir and Freundlich isotherm adsorption models as well as pseudo-first-order and pseudo-second-order kinetic models.

[0051] The wastewater pollutant simulation platform was constructed as follows: 5 mg of RM-MIL material was added to a 20 mL volume of the aforementioned dyes at a concentration of 20 mg / L. The dyes were then poured into a conical flask and subjected to adsorption reactions on an oscillator. Every hour, 5 mL of the solution was centrifuged from the conical flask, and the supernatant was tested to determine the absorbance of the different dyes. Subsequently, a photocatalytic degradation experiment was conducted using methylene blue as a pollution source. 5 mg of sample was added to 20 mL of methylene blue solution, and when adsorption equilibrium was reached, the sample was tested in a multifunctional photochemical reactor. Throughout the photocatalytic degradation of methylene blue, a 500 W mercury lamp was used as the light source. Every 30 minutes, 5 mL of solution was aspirated from the reaction system and centrifuged. The supernatant was collected and its absorbance measured. Upon completion, the aspirated solution was returned to the reaction system to continue the photocatalytic degradation reaction until the absorbance of the solution stabilized.

[0052] 1. Adsorption test of different dyes on the prepared composite material RM-MIL

[0053] The effects of RM-MIL on four model dyes, methyl violet, methylene blue, gentian violet and rhodamine B, were studied. The adsorption capacity of RM-MIL for different dyes increased continuously with time. Within 6 hours, the adsorption capacity of RM-MIL for rhodamine B reached 76 mg / g, the adsorption capacity for methylene blue reached 70.85 mg / g, the adsorption capacity for gentian violet reached 64.12 mg / g, and the adsorption capacity for methyl violet reached 52.54 mg / g, indicating that the composite materials can effectively remove these four model dyes.

[0054] 2. Adsorption of methylene blue at different concentrations on the prepared composite material RM-MIL

[0055] Using methylene blue as the adsorbate, the effects of RM-MIL on methylene blue solutions of varying initial concentrations (10 mg / L, 15 mg / L, 20 mg / L, and 25 mg / L) were investigated. As the concentration of the methylene blue solution increased, the material's adsorption capacity also increased. However, as the concentration of the methylene blue solution continued to increase, the number of adsorption sites occupied by the molecules increased, and the adsorption rate of the model dye decreased. The adsorption capacity of RM-MIL reached 74.28 mg / g, and the adsorption rate of RM-MIL reached 92.85%. Initially, the dye removal rate from the solution was rapid, primarily due to two factors: ① The initial high dye concentration resulted in strong electrostatic interactions between the adsorbent and the dye; and ② The adsorbent material, which had not yet been adsorbed, initially exposed a large number of active adsorption sites in the solution, making it more susceptible to adsorption of the model dye molecules during the adsorption process.

[0056] 3. Photocatalytic degradation of methylene blue on the prepared composite material RM-MIL

[0057] Under light-shielded conditions, after RM-MIL reached saturated adsorption of methylene blue, its photocatalytic degradation of methylene blue in solution was studied. Within 150 minutes, 64.4% of the methylene blue was degraded. The removal rate of methylene blue after adsorption-photocatalytic treatment exceeded 97%, demonstrating that the composite material RM-MIL prepared by the present invention can effectively remove organic pollutants from wastewater and has application value in wastewater treatment.

[0058] 4. The Langmuir isotherm adsorption model and the Freundlich isotherm adsorption model of the prepared composite material RM-MIL for adsorbing methylene blue were fitted.

[0059] Freundlich isotherm adsorption determination of model dye adsorption, RM-MIL correlation coefficient R 2 The correlation coefficient R of RM-MIL for the adsorption of model dyes by Langmuir isotherm adsorption is 0.984, and the correlation coefficient R of RM-MIL for the adsorption of model dyes by Langmuir isotherm adsorption is 0.9958. The data show that the material has a good correlation with the adsorption of model dyes. The correlation of Langmuir isotherm adsorption of RM-MIL is better than that of Freundlich isotherm adsorption, indicating that the adsorption of model dyes by RM-MIL conforms to the Langmuir isotherm adsorption and the adsorption of model dyes by RM-MIL belongs to the monolayer adsorption under the ideal adsorption system.

[0060] 5. Pseudo-first-order kinetics and pseudo-second-order kinetics fitting were performed on the prepared composite material RM-MIL.

[0061] To further explore the adsorption principle, the Langmuir and Freundlich isotherm adsorption models were used to explore the relationship between adsorption amount and equilibrium concentration. The Langmuir isotherm adsorption is based on monolayer adsorption, and adsorption occurs on the surface of the material. The linear equation of the Langmuir isotherm adsorption model is:

[0062]

[0063] Where, Qm: maximum adsorption capacity (mg / g), K L is the Langmuir constant. The Freundlich isotherm is another adsorption isotherm and is an empirical formula. The linear equation of the Freundlich isotherm adsorption model is as follows:

[0064]

[0065] Where K F is the Freundlich constant, is the adsorption index, and n is a parameter related to the strength of the interaction between the adsorbed molecules and the adsorption surface.

[0066] The adsorption kinetics of MIL and RM-MIL in four methylene blue solutions with different initial concentrations were studied using pseudo-first-order and pseudo-second-order kinetic linear models. The pseudo-first-order and pseudo-second-order kinetic linear model equations are shown below:

[0067] Where k1 is the pseudo first-order kinetic adsorption rate constant (s- 1 ), Q t is the adsorption amount at time t (mg / g), k2 is the pseudo-second-order kinetic rate constant (g·mg- 1 ·s- 1 ).

[0068] The Langmuir and Freundlich isotherm adsorption models were used to explore the relationship between adsorption amount and equilibrium concentration: Freundlich isotherm adsorption was used to determine the adsorption of the model dye, and the correlation coefficient R between RM and MIL was 2 The correlation coefficient R between RM and MIL was 0.984. 2 It is 0.9958. The data show that the functional material has a good correlation with the adsorption of model dyes. The correlation of Langmuir isotherm adsorption of RM-MIL is better than that of Freundlich isotherm adsorption, indicating that the adsorption of model dyes by RM-MIL conforms to the Langmuir isotherm adsorption.

[0069] The pseudo-second-order R 2 Both are greater than the pseudo first-order R2 Therefore, the material is more consistent with pseudo-second-order kinetics. Pseudo-second-order kinetics assumes that the adsorption process is influenced by chemical adsorption. Therefore, the adsorption of the model dye by RM-MIL material is mainly chemical adsorption.

[0070] The functional material RM-MIL, prepared through an in-situ composite method, can effectively remove 97.6% of organic pollutants from ambient water through an adsorption-degradation process. The composite material and its treatment process developed in this invention have broad application value in the field of wastewater treatment and also provide a feasible method for the resource recovery of red mud, a waste product of the Bayer process.

[0071] The basic principles, main features, and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are merely illustrative of the principles of the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention. Such changes and modifications are intended to fall within the scope of the present invention. The scope of protection claimed in the present invention is defined by the appended claims and their equivalents.

Claims

1. A functional material based on red mud waste loaded Fe-MOF, characterized in that: The functional material is in powder form, and its microstructure is rod-shaped crystalline Fe-MOF (MIL) loaded on block red mud.

2. The photocatalytic material based on red mud waste loaded Fe-MOF according to claim 1, characterized in that: When not loaded with red mud, the particle size of Fe-MOF (MIL) alone is 2 μm, and after being loaded with red mud, the particle size increases to 4.5 μm.

3. The method for preparing a photocatalytic material based on red mud waste loaded Fe-MOF according to claim 1, characterized in that The following steps are involved: (1) Acid treatment of red mud: Grind a certain amount of dry red mud, disperse it in a container filled with distilled water, stir it with an orbital oscillator, adjust the pH of the solution to 5, heat the obtained turbidity to boiling to obtain semi-dried red mud, and dry it to obtain acidified red mud powder; (2) Preparation of photocatalytic materials based on red mud waste loaded with Fe-MOF: Acidified red mud powder was added and dispersed in Fe 3+ The reaction was carried out in a DMF solution with 2-aminoterephthalic acid as the metal center and high temperature reflux reaction. After the reaction was completed, the solution was cooled to room temperature, centrifuged, washed and dried to obtain the functional material loaded with Fe-MOF (MIL), namely the composite photocatalytic material RM-MIL.

4. The method for preparing a functional material based on red mud waste loaded Fe-MOF according to claim 1, characterized in that: In the step (2), FeCl3·6H2O is used as Fe 3+ Source, firstly, Fe-MOF was prepared to obtain its yield, and based on this, the amount of FeCl3·6H2O, 2-aminoterephthalic acid and acidified red mud powder added when preparing functional materials was determined. The results showed that the ideal conditions for preparing red mud waste loaded Fe-MOF (MIL) functional materials are: the molar ratio of FeCl3·6H2O to 2-aminoterephthalic acid is 1:1, and the amount of acidified red mud powder added is twice the sum of the masses of FeCl3·6H2O and 2-aminoterephthalic acid.

5. The method for preparing a functional material based on red mud waste loaded Fe-MOF according to claim 1, characterized in that: In the step (2), the temperature of the high temperature reflux reaction is 120° C., and the reflux reaction time is 4 hours.

6. Use of the functional material based on red mud waste loaded Fe-MOF according to claim 1 in the adsorption and photocatalytic degradation of organic pollutants in sewage.

7. The use according to claim 6, characterized in that: Methylene blue, methyl violet, rhodamine B and gentian violet were selected as model dyes to study the adsorption performance of the functional material RM-MIL on different dyes. Then, methylene blue was used as the pollution source to test its photocatalytic degradation performance.

8. The use according to claim 7, characterized in that: 5 mg of the functional material based on Fe-MOF loaded with red mud waste was added to different dyes with a concentration of 20 mg / L and a volume of 20 mL. The above dyes were poured into a conical flask and adsorption reaction was carried out on an oscillator. 5 mL of the solution was taken from the conical flask for centrifugation every 1 h, and the supernatant was taken for testing to determine the absorbance values ​​of different dyes.

9. The use according to claim 7, characterized in that: 5 mg of the functional material based on red mud waste loaded Fe-MOF was added to 20 mL of methylene blue solution. When the adsorption equilibrium was reached, it was tested in a multifunctional photochemical reactor. During the entire process of photocatalytic degradation of methylene blue dye, a 500 W mercury lamp was used as the light source. Every 30 min, 5 mL of solution was aspirated from the reaction system for centrifugation, and the supernatant was taken to measure the absorbance value of the solution.

10. The use according to claim 9, characterized in that: The adsorption capacity of methylene blue by the functional material based on red mud waste loaded Fe-MOF reached 73.28 mg / g, and the total removal rate reached 97.6%.

Citation Information

Cited By

  • Method for preparing cement-based composite material through in-situ growth of Fe-MOF

    CN120058297A

  • Method for preparing cement-based composite material by in-situ growth of fe-mof

    CN120058297B